Hydroxyethyl starch 130/0.4 compared with 0.9% NaCl administered to greyhounds with haemorrhagic shock. (May 2017) - McBride, Duana; Raisis, Anthea L.; Hosgood, Giselle; Smart, Lisa
Abstract: Objective: To determine the cardiovascular and acid-base effects of 6% hydroxyethyl starch (HES) 130/0.4 and 0.9% sodium chloride (NaCl) administered to anaesthetized greyhounds with haemorrhagic shock. Study design: Prospective, experimental, complete randomized block design. Animals: Twelve healthy adult greyhounds. Methods: After 60 minutes of isoflurane anaesthesia, 48 mL kg −1 of blood was removed to induce hypotension. Dogs were randomized to receive either 20 mL kg −1 of HES 130/0.4 or 80 mL kg −1 of 0.9% NaCl over 20 minutes. Haemoglobin, arterial and central venous blood gas and electrolytes, lactate, mean arterial pressure (MAP) and cardiac index were measured at: T0, 60 minutes after induction of anaesthesia, immediately prior to blood removal; T1, immediately after blood removal; T2, immediately after fluid administration; and T3, 40 minutes after fluid administration. Oxygen extraction ratio (O2 ER) was calculated at each sample time. Results: O2 ER increased at T1 and decreased at T2 and T3, with no difference between the two groups. Dogs administered HES 130/0.4 had higher lactate at T2 [mean (95% confidence interval) 1.3 (0.8–1.9) mmol L −1 ] than dogs administered 0.9% NaCl [0.8 (0.5–1.1) mmol L −1 ]; p  = 0.045. Dogs administered HES 130/0.4 had a higher MAP at T3 [88 (74–102) mmHg] than dogs administered 0.9% NaCl [69 (60–79) mmHg]; p  = 0.019. Dogs administered 0.9% NaCl were more acidaemic at T2 and T3, including higher hydrogen ion, lower bicarbonate, lower base excess and higher chloride concentrations. Conclusion: and clinical relevance The effect of 20 mL kg −1 of HES 130/0.4 on shock, as measured by O2 ER, was no different than that of 80 mL kg −1 of 0.9% NaCl in dogs under general anaesthesia. Acidaemia in the NaCl group is likely attributable to hyperchloraemic metabolic acidosis from the larger volume administered.